LA ORIENTACIÓN DE LAS IGLESIAS ANDINAS DE LA REGIÓN DE ARICA Y PARINACOTA, CHILE: UNA APROXIMACIÓN ARQUEOASTRONÓMICA - Gangui, Alejandro (2017)
The heritage Andean churches of Arica and Parinacota are representative of the majority of Christian churches in the region. Judging by their architecture, materiality and decoration, they have many features in common and are faithful to the intentions of their original builders. However, their geographical locations and the landscape that surrounds these churches show specific features for each of them. In particular, the orientation of the main axes (towards the altar of the churches) shows some diversity. In this extended area, with little attention from parish priests, the local Aymara culture, with its own worldview, surely engaged in a dialogue with the Western tradition in order to design and build the Indian Reductions. In this paper we present the results obtained from the analysis of the precise spatial orientations of all the cataloged churches, employing the tools of archaeoastronomy, as a complement to the architectural, historical and cultural research of the temples. We also comment briefly on some progress that we hope to make in neighboring areas to the region here studied, which include a large number of very old temples and are part, along with the churches here considered, of a common and widespread cultural koine.